Lichen as biomonitor of atmospheric elemental composition from Potter Peninsula, 25 de Mayo (King George) Island, Antarctica - Mariana S Rivera; Soledad Perez Catan; Carla Di Fonzo; Laura Dopchiz; Maria A Arribere; Martin Ansaldo; Maria I Messuti; Debora F Bubach (Annals of Marine Science - Peertechz Publications, 2018)
Lichens are powerful biomonitor of airborne pollution around point sources or long range transport because they are perennial allowing bioindication at long period. The element concentrations in foliose and fruticose lichen species from Potter Peninsula located in 25 de Mayo (King George) Island is reported. The coefficient of the variation for most of the elements was up to 50% except for as and Br, K and Se. The Principal Component Analysis showed differences among sampling sites according to human activities respect to the special protected areas. Aluminium, Cr, Hg, Pb and Se concentrations are linked local waste burning, global inputs, and the melt-water processes, while Br and Se were associated with marine biogenic cycle. This information could be a valuable tool for future atmospheric studies.